Energy‐efficient resource allocation in heterogeneous networks with cell range expansion. Issue 4 (1st July 2015) - Jiang, Jiamo; Peng, Mugen; Li, Lei; Wang, Wenbo
Abstract : Cell range expansion (CRE) has emerged as a promising technique to improve spectral and energy efficiency (EE) in heterogeneous networks (HetNets). In this study, a resource allocation (RA) problem for maximising the EE is formulated with the considerations on CRE and cross‐tier interference coordination (CTIC). Owing to the forms of the objective function and the constraints, the optimisation problem is non‐convex and intractable. To solve this problem efficiently, we convert the original problem into an equivalent problem. Then, an efficient iterative algorithm is proposed, where the closed‐form expressions of power and resource block allocations are derived by Lagrange dual decomposition method in each iteration. It has been revealed that the proposed iterative algorithm converges to the energy‐efficient RA solutions. Compared with the algorithm without CTIC, the simulation results present that the proposed algorithm can achieve the EE gains by 70 percents when the number of the expanded‐range users is large and the quality of service requirement is high.